PENGARUH PROFITABILITAS, LIKUIDITAS, STRUKTUR KEPEMILIKAN, UKURAN PERUSAHAAN DAN OPINI AUDIT TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PERUSAHAAN - Hastutik, Suci (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
The purpose of this study was to analyze the influence of profitability, liquidity, ownership structure, company size, and audit opinion on the timeliness of financial reporting on financial services company listed on the Indonesia Stock Exchange in 2011 – 2013. The results were obtained conclusion: Profitability positive effect is not significant to the timeliness of financial reporting on financial services company listed on the Indonesia Stock Exchange in 2011 – 2013. Liquidity positive and significant impact on the timeliness of financial reporting on financial services company listed on the Indonesia Stock Exchange in 2011 – 2013. The ownership structure is not significant positive effect on the timeliness of financial reporting on financial services company listed on the Indonesia Stock Exchange in 2011 – 2013. The size of the company and a significant positive impact on the timeliness of financial reporting on financial services company listed on the Indonesia Stock Exchange in 2011 – 2013. Audit opinion positive and significant impact on the timeliness of financial reporting on financial services company listed on the Indonesia Stock Exchange in 2011 – 2013. Profitability, liquidity, ownership structure, company size, and audit opinion simultaneously significant effect on the dependent variable is the timeliness of financial reporting on financial services company listed on the Indonesia Stock Exchange in 2011 – 2013. Keywords: profitability, liquidity, ownership structure, company size, the audit opinion and timeliness of financial reporting